2022
DOI: 10.2147/ndt.s380353
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Damage of Lymphocytes in Patients with Acute Relapse of Schizophrenia: A Correlational Study with Efficacy and Clinical Symptoms

Abstract: Objective Accumulating evidence has demonstrated that schizophrenia is associated with mitochondrial and immune abnormalities. In this pilot case–control study, we investigated the level of mitochondrial impairment in lymphocytes in patients with acute relapse of schizophrenia and explored the correlation between the level of mitochondrial damage and symptoms or treatment response. Methods Lymphocytic mitochondrial damage was detected using mitochondrial fluorescence st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Some studies suggest that the elevated CD4+/CD8+ ratio may be linked to negative symptoms in schizophrenia (such as attention deficits and emotional blunting) ( 43 ), with a weaker association observed with positive symptoms (such as hallucinations and delusions), which contrasts with our research findings. Conversely, other studies have not identified any correlation between this ratio and specific symptom types ( 13 ). Similarly, research findings regarding the relationship between age and the T lymphocyte mitochondrial CD4+/CD8+ ratio are also subject to controversy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Some studies suggest that the elevated CD4+/CD8+ ratio may be linked to negative symptoms in schizophrenia (such as attention deficits and emotional blunting) ( 43 ), with a weaker association observed with positive symptoms (such as hallucinations and delusions), which contrasts with our research findings. Conversely, other studies have not identified any correlation between this ratio and specific symptom types ( 13 ). Similarly, research findings regarding the relationship between age and the T lymphocyte mitochondrial CD4+/CD8+ ratio are also subject to controversy.…”
Section: Discussionmentioning
confidence: 71%
“…Mitochondria, the energy-producing centers within cells, are crucial for normal cellular functioning. Some studies have indicated impaired lymphocyte mitochondrial function in patients receiving treatment with atypical antipsychotic medications( 13 ). Furthermore, the metabolic syndrome induced by medication may contribute to lymphocyte mitochondrial damage ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SCMM exhibited a good performance in predicting the response to treatment for schizophrenia. 16 In addition, lymphocyte dysfunction occurs in T cells during the early stages of sepsis. SCMM-CD4 is more effective for diagnosing sepsis at an early stage than the traditional biomarker PCT, and the diagnostic value of PCT, when combined with SCMM-CD4, is superior to that observed for SCMM-CD4 alone during early sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…However, their findings on the expression of dopamine receptors D (DRD) 2 and 4 were inconsistent, likely due to methodological differences (mRNA expression vs. flow cytometry) [ 173 , 174 ]. T-cell-specific oxidative damage in SCZ has also been quantified and showed an increase in mitochondrial dysfunction across different T cell subsets from patients with acute relapse compared to HCs [ 175 ]. Furthermore, this cellular pathology appears to be associated with positive symptoms [ 175 ].…”
Section: Alterations In Circulating Immune Cells In Sczmentioning
confidence: 99%
“…T-cell-specific oxidative damage in SCZ has also been quantified and showed an increase in mitochondrial dysfunction across different T cell subsets from patients with acute relapse compared to HCs [ 175 ]. Furthermore, this cellular pathology appears to be associated with positive symptoms [ 175 ]. Lastly, T cell methylation profile and repertoire were reportedly associated with distinct SCZ subtypes.…”
Section: Alterations In Circulating Immune Cells In Sczmentioning
confidence: 99%